2010
DOI: 10.1016/j.janxdis.2009.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Eye tracking and visual attention to threating stimuli in veterans of the Iraq war

Abstract: Theoretical and clinical characterizations of attention in PTSD acknowledge the possibility for both hypervigilance and avoidance of trauma-relevant stimuli. This study used eye tracking technology to investigate visual orientation and attention to traumatic and neutral stimuli in nineteen veterans of the Iraq War. Veterans saw slides in which half the screen had a negatively valenced image and half had a neutral image. Negatively valenced stimuli were further divided into stimuli that varied in trauma relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
122
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(133 citation statements)
references
References 54 publications
9
122
1
1
Order By: Relevance
“…Although not instructed, controls may have spontaneously engaged in attentional deployment, another form of early emotion regulation (Gross 2008). Previous eye-tracking studies have shown that PTSD is related to attentional bias for trauma-related stimuli, accompanied by greater autonomic arousal, compared with trauma-exposed controls (Felmingham et al 2011;Kimble et al 2010).…”
Section: Discussionmentioning
confidence: 93%
“…Although not instructed, controls may have spontaneously engaged in attentional deployment, another form of early emotion regulation (Gross 2008). Previous eye-tracking studies have shown that PTSD is related to attentional bias for trauma-related stimuli, accompanied by greater autonomic arousal, compared with trauma-exposed controls (Felmingham et al 2011;Kimble et al 2010).…”
Section: Discussionmentioning
confidence: 93%
“…In addition, there is literature that supports the validity of the dot probe in assessing attention bias in traumatized individuals (Lindstrom et al 2011, Fani et al 2012, Fani et al 2013). However, future research should employ other, promising approaches to the assessment of attention bias, such as eye tracking methodologies (Kimble et al 2010). Lastly, our population consisted of adults recruited from general care hospital waiting rooms who may have already developed anxiety, depression, or PTSD.…”
Section: Discussionmentioning
confidence: 99%
“…However, other cross-sectional research finds that veterans with elevated PTSD symptoms show an attentional bias toward negative images compared to veterans with low levels of PTSD symptoms (33,34). One possible explanation for these divergent findings is that attentional avoidance may be particularly relevant for predicting anxiety responses to acute stressors, whereas attentional vigilance may occur after the onset of PTSD.…”
Section: Depressive Symptomsmentioning
confidence: 94%